The Use of Wordwall in the Direct Method for Teaching Arabic Vocabulary at Manba’ul Ulum Islamic Senior High School - Muhammad Faris Setiawan; Iman Matin; Muhammad Fahri (INTIFA: Journal of Education and Language, 2026)
Mastering vocabulary is a fundamental foundation in learning Arabic. Previous research has only used Wordwall as a separate evaluation tool, without integrating it with a specific methodology and teaching method. This study aims to determine: (1) how to use Wordwall in the direct method for teaching vocabulary at SMA Manbaul Ulum  and (2) its impact on vocabulary mastery. The study employed a quasi-experimental method with a pretest-posttest design for tenth-grade students on the topic "الطعام والشراب". The experimental group used Wordwall and the direct method, while the control group used the traditional method. Data were analyzed using Shapiro-Wilk, homogeneity, t-test, and N-Gain tests with SPSS Statistics 25. The results showed that the use of Wordwall in the direct method had a significant effect. The experimental group's scores increased from 56.41 to 82.76, while the control group increased from 60.52 to 76.41. The t-test showed Sig. (2-Tailed) = 0.037 < 0.05, thus H₀ was rejected and H₁ was accepted. The N-Gain value of 0.61 (moderate category) proves that the integration of Wordwall and the direct method is effective in improving vocabulary mastery in a real communicative context. This study enriches the digital Arabic language learning literature with an integrative model in Indonesian Islamic senior high schools.